Practical Applications and Blast Designs with Nonelectric Initiation Systems - Tom Treleaven (International Society of Explosives Engineers, 1991)
Several nonelectric blast initiation systems have been developed since the mid 1970's. Until that time, most blasts were initiated either electrically with electric blasting caps or nonelectrically with detonating cord. What the development of these new systems was attempting to accomplish was to provide a system that was nondisruptive to the stemming or explosive column, but still possessed the safety and flexibility inherent in nonelectric systems.